A realist evaluation of social prescribing: an exploration into the context and mechanisms underpinning a pathway linking primary care with the voluntary sector. Issue 3 (7th December 2017) - Bertotti, Marcello; Frostick, Caroline; Hutt, Patrick; Sohanpal, Ratna; Carnes, Dawn
Abstract : This article adopts a realist approach to evaluate a social prescribing pilot in the areas of Hackney and City in London (United Kingdom). It unpacks the contextual factors and mechanisms that influenced the development of this pilot for the benefits of GPs, commissioners and practitioners, and reflects on the realist approach to evaluation as a tool for the evaluation of health interventions. Primary care faces considerable challenges including the increase in long-term conditions, GP consultation rates, and widening health inequalities. With its emphasis on linking primary care to non-clinical community services via a social prescribing coordinator (SPC), some models of social prescribing could contribute to reduce the burden on primary care, tackle health inequalities and encourage people to make greater use of non-clinical forms of support. This realist analysis was based on qualitative interviews with users, commissioners, a GP survey, focus groups and learning events to explore stakeholders' experience. To enable a detailed analysis, we adapted the realist approach by subdividing the social prescribing pathway into stages, each with contextual factors, mechanisms and outcomes. SPCs were pivotal to the effective functioning of the social prescribing service and responsible for the activation and initial beneficial impact on users. Although social prescribing shows significant potential for the benefit of patients and primary care, several challenges need to be considered and overcome, including 'buy in' from some GPs, branding, and funding for the third sector in a context where social care cuts are severely affecting the delivery of health care. With its emphasis on context and mechanisms, the realist evaluation approach is useful in understanding how to identify and improve health interventions, and analyse in greater detail the contribution of different stakeholders. As the SPC is central to social prescribing, more needs to be done to understand their role conceptually and practically.